2009
DOI: 10.1002/lt.21745
|View full text |Cite
|
Sign up to set email alerts
|

Extended right liver grafts obtained by an ex situ split can be used safely for primary and secondary transplantation with acceptable biliary morbidity

Abstract: Split liver transplantation (SLT) is clearly beneficial for pediatric recipients. However, the increased risk of biliary complications in adult recipients of SLT in comparison with whole liver transplantation (WLT) remains controversial. The objective of this study was to investigate the incidence and clinical outcome of biliary complications in an SLT group using split extended right grafts (ERGs) after ex situ splitting in comparison with WLT in adults. The retrospectively collected data for 80 consecutive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 42 publications
5
50
1
1
Order By: Relevance
“…In our study, the cold ischemia time was not correlated with the development of S4‐related complications. The median cold ischemia time was found to be comparable to that of previous studies 33, 35. In our series, we demonstrated that S4‐related complications were directly associated with high rates of graft loss (50%) and mortality (8.3%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the cold ischemia time was not correlated with the development of S4‐related complications. The median cold ischemia time was found to be comparable to that of previous studies 33, 35. In our series, we demonstrated that S4‐related complications were directly associated with high rates of graft loss (50%) and mortality (8.3%).…”
Section: Discussionsupporting
confidence: 87%
“…In a radiological study of living donors, Yeh et al34 highlighted the importance of biliary tree vascularization and demonstrated that the distance between the second‐order biliary branch and the corresponding hepatic artery was a predictor of biliary leaks. Takebe et al35 identified cholestatic disease as a significant risk factor for bile leakage from the cut surface but could not offer a satisfactory explanation for this observation. Goss et al36 highlighted the devascularization of biliary convergence and graft rewarming during back‐table procedures as important risk factors in the development of ischemia/reperfusion injury and biliary complications.…”
Section: Discussionmentioning
confidence: 94%
“…The risk of bile leaks from the cutsurface is higher than after LDLT; e.g. in the Hanover experience 15% cut surface leaks were observed (87). Most cut surface leaks have a favourable managed either by percutaneous drainage or surgical revision (87).…”
Section: Special Issues In Split and Pediatric Liver Transplantationmentioning
confidence: 99%
“…in the Hanover experience 15% cut surface leaks were observed (87). Most cut surface leaks have a favourable managed either by percutaneous drainage or surgical revision (87). Although available evidence is sparse, some authors recommend routine use of fibrin glue or fibrin-collagen sponges for prophylaxis of cut-surface leaks (88).…”
Section: Special Issues In Split and Pediatric Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation